Empowering Local Communities Through Community-Based Tourism: A Case Study Of Tangkit Village - Dinda Rosanti Salsa Bela; Mirza Sazeta; Arissy Jorgi Sutan; Azira Novia Rizal (Indonesian Journal Publisher, 2026)
This study aims to examine how Community-Based Tourism (CBT) empowers local communities in Tangkit Village through economic, social, and cultural dimensions. Tangkit Village, located in Jambi Province, is known for its pineapple-based agro-tourism and Malay cultural heritage, making it a unique rural tourism destination. While CBT has been widely explored globally, most research emphasizes broad sustainability frameworks, leaving a gap in micro-level empowerment strategies within Indonesian rural contexts. Addressing this gap, the study introduces novelty by analyzing CBT’s role in fostering income generation, cultural preservation, and participatory governance in a localized setting. Using a qualitative approach, secondary data were analyzed through NVivo 12 Plus employing Crosstab Query and Word Frequency tools to identify dominant themes. Results indicate that income generation (54.55%) and community participation in tourism management (50%) are the strongest impacts, while cultural integration is evident through tourism packages (44.44%). However, skill development (20%) and micro-enterprise growth (18.18%) remain limited, signaling areas for improvement. The study concludes that CBT enhances livelihoods and cultural identity but requires stronger capacity-building and inclusive governance. Limitations include reliance on secondary data and a single-case focus, restricting generalizability. Future research should incorporate primary data, comparative case studies, and longitudinal designs to assess scalability and resilience. Exploring digital innovations for marketing and training is also recommended to strengthen CBT practices. These findings contribute to advancing sustainable and inclusive tourism development in rural Indonesia.